HPLC tracing of sennosides and quality control study of laxative herbal medicine “Al-Halol” - Ahmed Aljameeli; Mohamed Ashour (Indonesian Journal of Pharmacy, 2022)
Al-Halol is a famous herbal recipe, formed of senna and supportive herbal remedies. It is distributed widely in the herbal markets of Saudi Arabia (KSA) and other Gulf countries. Al-Halol is prescribed for intestinal evacuation and treatment of different forms of constipation. The aim of the present study was to deal with the quality control (QC) status of three different formulations of “Al-Halol” (Lax-1, Lax-2 and Lax-3). A simple method was designed for isolation of crude sennosides fraction from standard senna leaves and utilized for HPLC tracing of sennosides in the tested herbal medicines along with several qualitative and quantitative QC tests. The present study revealed tentatively the presence of 3.6 % senna pods, 29.1% senna leaves and 22.6 % senna leaves as principle material in Lax-1, Lax-2 and Lax-3 respectively, percentage of intestinal motility in mice was also determined as 28.4%, 65.19% and 60.73% for Lax-1, Lax-2 and Lax-3 respectively compared with negative control (54.78%), and positive controls (i.e. senna leave extract = 81.2 %, and bisacodyl =76.7 %). There was a statistically significant difference between all groups (p value < 0.001), except between standard senna leaves extract and bisacodyl and between Lax-2 and Lax-3 extracts. However, great variations have been recorded between the different samples. The present work provides a simple method for isolation and HPLC tracing of sennosides in senna drugs. It is the first time for evaluation and QC study of these laxative herbal formulations.